ENT600 : Smart Organic Bin / Nurul Ain Athirah Muhamad, Haslinda Rahim and Nurfarah Hidayu Abdul Rahman - Muhamad, Nurul Ain Athirah; Rahim, Haslinda; Abdul Rahman, Nurfarah Hidayu (2018)
This New Product Development report is about developing a new product, Smart Organic Bin, that has been improved and revised to replace the existing product. The function of this product is to recycle the food waste into ready-to-use fertilizer that can be used for gardening or landscaping. It is to overcome the problem of excessive food waste in household. The main target of the market is households. In the beginning of the process, the information is collected by using questionnaire and online poll from 10 respondents which are students and working ladies. In R&D, the team came out with two options (Option A and Option B) of ideas in the stage of idea generation. Both options were evaluated based on the innovative product features. The ideas of the product undergo market survey which the result is 80% of respondents chose Option B while 20% chose Option A. The working prototype of selected idea (Option B) is distributed to the 10 households for test marketing. The team collected their feedbacks towards the product. All the respondents would buy the product.